Anisotropic and Heterogeneous Development of Microstructures. Combining Laboratory/Synchrotron X-rays and EBSD on a few SPD Metallic Systems - Bolmaro, Raul Eduardo (2014)
The onset of Severe Plastic Deformation (SPD) regime is quite instructive on the possible origins of the nano-microstructures developed in metals and alloys. It is known that grain fragmentation and dislocation accumulation, among other defects, proceed at different paces depending fundamentally on grain orientations and active deformation mechanisms. There have been many attempts to characterize nano-microstructure anisotropy, leading all of them to sometimes contradictory conclusions. Moreover, the characterizations rely on different measurements techniques and pos-processing approaches, which can be observing different manifestations of the same phenomena. On the current presentation we show a few experimental and computer pos-processing and simulation approaches, applied to some SPD/alloy systems. Williamson-Hall and Convolutional Multiple Whole Profile (CMWP) techniques will be applied to peak broadening analysis on experimental results stemming from laboratory Cu Ka X-rays, and synchrotron radiation from LNLS (Laboratório Nacional de Luz Síncrotron, Campinas, Brazil) and Petra III line (HEMS station, at DESY, Hamburg, Germany). Taking advantage of the EBSD capability of giving information on orientational and topological characteristics of grain boundaries, microstructures, grain sizes, etc., we also performed investigations on dislocation density and Geometrically Necessary Dislocation Boundaries (GNDB) and their correlation with texture components. Orientation dependent nano-microstructures and domain sizes are shown on the scheme of generalized pole figures and discussions provide some hints on nano-microstructure anisotropy.